The effect of course length on individual medley swimming performance in national and international athletes - Wolfrum, M.; Rüst, C. A.; Rosemann, T.; Lepers, R.; Knechtle, B. (Journal of Human Kinetics, 2014)
Effects of course length (25 m versus 50 m) and advances in performance of individual medley swimming were examined for men and women in Swiss national competitions and FINA World Championships during 2000-2011. Linear regression and analysis of variance (ANOVA) were used to analyse 200 m and 400 m race results for 26,081 swims on the Swiss high score list and 382 FINA finalists. Swiss and FINA swimmers of both sexes were, on average, 4.3±3.2% faster on short courses for both race distances. Sex-related differences in swim speed were significantly greater for FINA swimmers competing in short-course events than in long-course events (10.3±0.2% versus 9.7±0.3%, p<0.01), but did not differ for Swiss swimmers (p>0.05). Sex-related differences in swimming speed decreased with increasing race distance for both short- and long-course events for Swiss athletes, and for FINA athletes in long-course events. Performance improved significantly (p<0.05) during 2000-2011 for FINA men competing in either course length and FINA females competing in short-course events, but not for Swiss swimmers. Overall, the results showed that men and women individual medley swimmers, competing at both national and international levels, have faster average swimming speeds on short courses than on long courses, for both 200 m and 400 m distances. FINA athletes demonstrate an improving performance in the vast majority of individual medley events, while performance at national level seems to have reached a plateau during 2000-2011.